Dynamic features of passive whole-spacecraft vibration isolation platform based on non-probabilistic reliability. (January 2015) - Zhang, Ye-wei; Fang, Bo; Zang, Jian
A whole-spacecraft vibration isolation platform can improve the dynamic environment during satellite launches. In this paper, the dynamic characteristics of a whole-spacecraft vibration isolation platform with uncertain parameters are investigated. The governing equation of the platform is derived and the non-probabilistic reliability theory is utilized to analyze the dynamic characteristics. Then, the numerical results are carried out and compared with the experimental data. It is found that non-probabilistic reliability theory is a powerful tool to reveal the dynamic characteristics, which may lead to a new design of the platform with enhanced security and reliability.